ALK-rearranged lung adenocarcinoma showing intra-bronchial protrusion: a case of actually peripheral origin with a rare spreading pattern - Noma, Daisuke; Inamura, Kentaro; Matsuura, Yosuke; Ninomiya, Hironori; Ichinose, Junji; Nakao, Masayuki; Mun, Mingyon; Ishikawa, Yuichi; Okumura, Sakae (Biotarget; Vol 1 (November 2017): Biotarget, 2017)
We present a case of anaplastic lymphoma kinase (ALK)-rearranged lung adenocarcinoma, which showed intra-bronchial protrusion, but was found to be immunohistochemically positive for thyroid transcription factor-1 (TTF-1). To the best of our knowledge, this is the first case of ALK-rearranged lung cancer that presented as an elevated lesion projecting into the bronchial lumen. Although the tumor was located to be close the hilar region of the lung, it showed a positive immunohistochemical expression of TTF-1, which implied the peripheral origin of the tumor. This case highlights the need to consider the possibility of an ALK-rearranged lung adenocarcinoma of peripheral origin masquerading as a central-type tumor.